2004
DOI: 10.1002/jez.b.21008
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects on mandibular morphology II: Differential epistasis and genetic variation in morphological integration

Abstract: The evolution of morphological modularity through the sequestration of pleiotropy to sets of functionally and developmentally related traits requires genetic variation in the relationships between traits. Genetic variation in relationships between traits can result from differential epistasis, where epistatic relationships for pairs of loci are different for different traits. This study maps relationship quantitative trait loci (QTLs), specifically QTLs that affect the relationship between individual mandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 42 publications
2
49
0
11
Order By: Relevance
“…In essence, a few QTLs with statistically significant effects are identified, and used to check whether hypothesized integrated traits share QTLs. Of particular interest for the evolution of pleiotropy and integration are studies of differential epistasis [83,84,103,183]. These studies identify relationship QTLs that modify the pleiotropic effects of other QTLs, and thus give evidence for genetic variation in trait covariance.…”
Section: Measurement Of Integration and Modularitymentioning
confidence: 99%
“…In essence, a few QTLs with statistically significant effects are identified, and used to check whether hypothesized integrated traits share QTLs. Of particular interest for the evolution of pleiotropy and integration are studies of differential epistasis [83,84,103,183]. These studies identify relationship QTLs that modify the pleiotropic effects of other QTLs, and thus give evidence for genetic variation in trait covariance.…”
Section: Measurement Of Integration and Modularitymentioning
confidence: 99%
“…Usually, the emphasis in the quantitative genetics literature is placed on correlation between traits being produced by pleiotropy , because linkage disequilibrium is usually thought to be transient (unless actively maintained by selection) due to recombination among loci. Recent studies of genetic architecture in many organisms, and especially in mammals, have found ample evidence of a modular organization with pleiotropic effects usually falling within phenotypic modules and being reduced among modules (Ehrich et al 2003;Cheverud et al 2004;Wagner et al 2008;Kenney-Hunt et al 2008). Accordingly, a prerequisite for the evolution of modularity is that pleiotropy must be genetically variable.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, there is discussion about whether the relationship between traits represents yet another phenotype that can be affected by genetic manipulation. Relationship QTL, or rQTL, which change the relationships between phenotypes have been identified in mice, 4,5 and are likely present in other organisms as well.…”
Section: Introductionmentioning
confidence: 99%